ANALISIS KUALITAS PELAYANAN PERPUSTAKAAN FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO - Buana, Indra Cakra; Sulandari, Susi; Mustam, Muhammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Libraries play an important role for the community and especially the world of education. Without information, people become marginalized and underdeveloped . Encountered symptoms of dissatisfaction with the services provided librarian Social and Political Science Faculty University Diponegoroyang shows service can not meet the expectations of students . Customer satisfaction is one indicator of the success of library services at the Faculty of Social and Political Sciences, Diponegoro University . Service is considered satisfactory if it can meet the expectations of its customers . This study aims to menganilisis criterion Community Satisfaction Index ( HPI ) is Procedures , Service Requirements , Clarity Services Officer , Disciplinary Services Officer , Services Officer Responsibilities , Capabilities Services Officer , Service Speed , Obtain Justice Service, politeness and hospitality Officer , Fairness Care Costs , Cost Assurance Services , Assurance Services Schedule , Leisure Environment , and Security service to customer satisfaction , menganilisis level of customer satisfaction in terms of the gap between the service user with the officer 's performance against the quality of library services in the Social and Political Science Faculty , Diponegoro University and explain the strengths and weaknesses service element in the fourteenth measurement criteria in the dimensions of service quality perceptions of customers . This study uses a quantitative approach to quantitativedeskripstif . The subjects of the study were 150 library patrons correspondent Social and Political Science Faculty , Diponegoro University that using simple random technique . The technique used is the analysis of the value of HPI ( Customer Satisfaction Index ) . The results showed that not all elements can work well to serve customers ( visitors ) library and the social sciences faculty of political science, Diponegoro University. The results of the data analysis of the fourteenth criteria tested, there is one element that is rated poor service schedule with the certainty of the value 2.36 of the service element, with a weight of 0.071 and the results is 0.016756. The results of the analysis with diagrams Kartisius Assessment Implementation and Assessment Interests Library Social and Political Science Faculty, Diponegoro University shows that discipline and speed of service personnel affect service user satisfaction. Although the results of the assessment of SMEs assessed that the performance of library services and the Social and Political Science Faculty,, Diponegoro University was good , with a 68.40 index.